The use of the two different mycotoxin deactivators in the nutrition of dairy cows - Igor Jajić; Saša Krstović; Miroslava Polovinski-Horvatović; Ivan Vojnić Purčar (Mljekarstvo)
The aim of this study was to investigate the effect of two different commercial products for mycotoxin deactivation in the dairy cows’ nutrition. The research was done on the 18 dairy cows in the different phase of lactation, with the average production of 14 L of milk per day. The diet contained in average 8 kg of concentrate feed, 10 kg of mixed peas and wheat forage, 4 kg hay of alfalfa and cereal straw ad libitum. Before starting the trials all components of the cows’ ration were analysed for the presence of aflatoxin B1, while cow’s milk was analysed for the presence of aflatoxin M1. In the first phase of the trial cows were fed diet containing aflatoxin B1 at level of 5±0.9 µg/kg, which resulted in the average aflatoxin M1concentration of 181±3.5 ng/kg in the milk. In the second phase of the trail 0.5% of the commercial product 1 (Neozel®) was added into the feed ration of cows and after the period of adaptation, the aflatoxin M1 concentration in milk was measured. In the third phase of the trail 0.3% of the commercial product 2 (miko-Stop 0.3®) was added into the feed ration of cows and also, after the period of adaptation, the concentration of aflatoxin M1 in milk was measured. The last phase was the control phase in which cows were fed diets with aflatoxin B1 (5 µg/kg) without added mycotoxin deactivators. The use of both commercial products for ten days resulted in the reduction of aflatoxin M1 levels for 35.9% and 53.6%, respectively.